فاعلية برنامج تدريبي مستند إلى نشاطات اللعب الفردية في تحسين مهارتي التقليد والاستجابة لدى عينة من أطفال اضطراب طيف التوحد في الأردن - الجدوع، عصام عبدالله الدويلة; المومني، محمد أحمد مجلي (الجامعة الأردنية - عمادة البحث العلمي, 2020)
The aim of this study was to investigate efficiency of a training program, based on individual playing activities, on improvement of imitation and responsiveness skills. The Pre-Methodology was applied. Study tools were Imitation and Responsiveness Scale for autism spectrum children and the training program. It was applied on (8) autism spectrum children after reaching their psychometric features. Results indicated significant effect on (a=0.05) prior and subsequent measure of imitation improvement attributed for the training program. Results also indicated significant effect on (a=0.05) prior and subsequent measure of responsiveness skills improvement attributed for the training program. In the light of the study, the researchers recommended the importance of inclusion of imitation and responsiveness skills as an prerequisite requirement for the educational and treatment programs for autism spectrum children.
هدفت هذه الدراسة إلى تقصي فاعلية برنامج تدريبي مستند إلى نشاطات اللعب الفردية في تحسين مهارتي التقليد والاستجابة، واستخدم المنهج ما قبل التجريبي، وتمثلت أدوات الدراسة بمقياس التقليد استجابة والاستجابة للأطفال التوحديين والبرنامج التدريبي، اللذين تم تطبيقهما على (8) أطفال من ذوي اضطراب طيف التوحد بعد أن تم التوصل إلى خصائصهما السيكومترية، وأشارت نتائج الدراسة إلى وجود أثر ذو دلالة إحصائية في مستوى (a=0.05) بين القياس القبلي والبعدي في تحسين مهارة التقليد يعزى إلى البرنامج التدريبي، كما أشارت النتائج أيضا إلى وجود أثر ذو دلالة إحصائية في مستوى (a=0.05) بين القياس القبلي والبعدي في تحسين مهارة استجابة الاستجابة يعزى إلى البرنامج التدريبي. وفي ضوء نتائج الدراسة أوصى الباحثان بضرورة اهتمام الاهتمام بتضمين مهارتي التقليد والاستجابة كمتطلب أساسي في البرامج التربوية والعلاجية للأطفال التوحديين.
Keywords: التربية الخاصة -- اضطراب طيف التوحد -- البرامج التعليمية -- التواصل اللغوي